Scutellaria Extract inhibits IL-22-induced hyperproliferation of human keratinocyte cell line HaCaT - ZENG Ying, FU Guili (Jichu yixue yu linchuang, 2023)
Objective To explore the experimental study of Scutellaria extract on IL-22-induced proliferation, apoptosis and inflammatory response of human keratinocyte cells line (HaCaT) via miR-369-3p. Methods HaCaT cells were divided into control group, IL-22 group (cell models, 100 ng/mL of IL-22 cultured cells), low, medium and high dose group (Scutellaria extract 50, 100, 150 μg/mL), anti-miR-NC intervention group (transfected anti-miR-NC), anti-miR-369-3p intervention group (transfected with anti-miR-369-3p), miR-NC+high-dose group (transfected with miR-NC, Scutellaria extract cultured cells), miR-369-3p+high-dose group (transfected with miR-369-3p, Scutellaria extract cultured cells). MTT experiment detected cell proliferation; Flow cytometry detected cell apoptosis; Western blot detected cleaved caspase-3 protein expression;ELISA detected TNF-α and IL-6 content; RT-qPCR detected miR-369-3p expression. Results Compared with the control group, the IL-22 group cell survival rate, miR-369-3p expression, TNF-α, IL-6 expression increased(PP＞0.05); Compared with the IL-22 group, the cell survival rate, miR-369-3p expression, TNF-α, IL-6 expression decreased in the low, middle and high dose groups, while the apoptosis rate, cleaved caspase-3 protein expression increased(PPConclusions Scutellaria extract inhibits IL-22-induced hyperproliferation and inflammatory response of human keratinocytes, and promotes apoptosis with potential mechanisms by inhibiting the expression of miR-369-3p.